Simulation of Inertially Stabilized Platforms - Sushchenko , Olha; Saluyk , Olexander; Yehorov , Serhii (Electronics and Control Systems, 2022)
The article describes the peculiarities of determining the characteristics of inertial stabilized platforms operating on land-based moving objects. A method for estimating the dynamic error and the influence of the unbalance moment is proposed. The possibilities of different ways of setting control signals during semi-natural tests were investigated. The results of experimental tests of inertial stabilized platforms intended for operation on ground moving objects are presented. The proposed approaches are important for evaluating the characteristics of the motion control system of the stabilized platform after performing its synthesis and organizing the process of semi-natural tests. The obtained results can be extended to inertial stabilized platforms of a wide class.